Hubungan Tingkat Pengetahuan tentang Covid-19 dengan Sikap Siswa Siswi Dalam Menerapkan Protokol Kesehatan Sekolah MAN 2 Jepara - Wahyu Kristiningrum; Risma Aliviani Putri; Widayati (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2022)
Covid-19 cases in Indonesia until February 2022 continue to grow. The increase in Covid-19 cases is due to the emergence of a new variant of the corona virus, namely Omicron. By following the Circular Letter of the governor of Central Java, face-to-face learning (PTM) is limited to 1 (one) class, only 50% of which enter every day. COVID-19 can be suppressed with a good level of knowledge and a positive attitude from students during school learning. to determine the relationship of the level of knowledge of students in schools about COVID-19 with the attitude of students in implementing health protocols during the COVID-19 pandemic.this study used a descriptive correlation design with a cros-sectional approach carried out in February 2022 at MAN 2 Jepara. The population in this study were all students of Class XII who attended the PTM amounted to 34 students. The sample in this study using a total sampling of 34 respondents. most of the students ' knowledge levels about COVID-19 were categorized as good, there were 24 respondents (70.6%), enough knowledge level as many as 2 respondents (5.9%) and those with less knowledge level were 8 respondents (23.5). Most of the students ' attitudes in implementing health protocols during the COVID-19 pandemic were categorized as positive as 22 respondents (64.7%) and adolescents with negative attitudes as many as 12 respondents (35.5%). there is a relationship between the level of knowledge of students in schools about COVID-19 and the attitude of students in implementing health protocols during the COVID-19 pandemic at MAN 2 Jepara. AbstrakKasus Covid-19 di Indonesia hingga Februari 2022 terus bertambah banyak. Peningkatan kasus Covid-19 ini dikarenakan munculnya virus corona varian baru, yaitu Omicron. Dengan mengikut surat edaran Gubernur Jawa tengah maka pembelajaran tatap muka (PTM) dilaksanakan terbatas dalam 1 (satu) kelas, hanya 50% yang masuk setiap harinya. COVID- 19 dapat ditekan dengan tingkat pengetahuan yang baik serta sikap yang positif dari siswa-siswi selama mengikuti pembelajaran di sekolah. Untuk mengetahui hubungan tingkat pengetahuan siswa-siswi di sekolah tentang COVID-19 dengan sikap siswa-siswi dalam menerapkan protokol kesehatan di masa pandemi COVID-19. Penelitian ini menggunakan desain deskriptif korelasi dengan pendekatan cros-sectional dilaksanakan pada bulan Febuari 2022 di MAN 2 Jepara. Populasi pada penelitian ini adalah seluruh siswa-siswi kelas XII yang hadir mengikuti PTM berjumlah 34 siswa. Sampel dalam penelitian ini mengunakan total sampling sejumlah 34 responden. sebagian besar tingkat pengetauan siswa-siswi tentang COVID-19 berkategori baik terdapat 24 responden (70,6%), tingkat pengetahuan cukup sebanyak 2 responden (5,9%) dan yang memiliki tingkat pengetahuan kurang 8 responden (23,5). Sebagian besar sikap siswa-siswi dalam menerapkan protokol kesehatan di masa pandemi COVID-19 berkategori positif sebanyak 22 responden (64, 7%) dan siawa-siswi dengan sikap negatif sebanyak 12 responden (35,5%). Terdapat hubungan antara tingkat pengetahuan siswa-siswi di sekolah tentang COVID-19 dengan sikap siswa-siswi dalam menerapkan protokol kesehatan di masa pandemi COVID-19 di MAN 2 Jepara.